2021
DOI: 10.1097/sla.0000000000005259
|View full text |Cite
|
Sign up to set email alerts
|

Long-Term Outcomes Following Elective Repair of Intact Abdominal Aortic Aneurysms

Abstract: Objective: Compare long-term mortality, secondary intervention and secondary rupture following elective endovascular aneurysm repair (EVAR) and open surgical repair (OSR). Background: EVAR has surpassed OSR as the most common procedure used to repair abdominal aortic aneurysm (AAA), but evidence regarding long-term outcomes is inconclusive. Methods: We included patients in linked clinical registry and administrative data undergoing EVAR or OSR for intact AAA between January 2010 and June 2019. We used an inver… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
13
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 10 publications
(14 citation statements)
references
References 27 publications
1
13
0
Order By: Relevance
“…Our finding of a consistent and early survival benefit of EVAR was supported by previous studies 9–16 . However, these studies showed varying lasting effects of the survival benefit ranging from 1 to 4 years 9–16 .…”
Section: Discussionsupporting
confidence: 88%
See 4 more Smart Citations
“…Our finding of a consistent and early survival benefit of EVAR was supported by previous studies 9–16 . However, these studies showed varying lasting effects of the survival benefit ranging from 1 to 4 years 9–16 .…”
Section: Discussionsupporting
confidence: 88%
“…The EVAR-1 trial examined aneurysm-related reinterventions 9 . Others examined aneurysm and procedure-related reinterventions, the definition of which also differed across studies 10–12,15,16 . Our study focused on repeat AAA repair and found that across all 3 countries, the reintervention rates were 2% to 3% after OAR and 8% to 9% after EVAR at 7 years.…”
Section: Discussionmentioning
confidence: 82%
See 3 more Smart Citations